Wolves of the Calla [compact disc, unabridged] - King, Stephen, 1947- (King, Stephen, 1947- Dark tower., 2003)
"Roland and his ka-tet are bearing southeast through the forests of Mid-World, the almost timeless landscape that seems to stretch from the wreckage of civility that defined Roland's youth to the crimson chaos that seems the future's only promise"--Container.